2000
DOI: 10.1046/j.1469-7580.2000.19630327.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localisation and size distribution of collagen fibrils in Glisson's sheath of rat liver: implications for mechanical environment and possible producing cells

Abstract: The ultrastructure and size distributions of collagen fibrils in Glisson's sheath were investigated in the rat liver to analyse the mechanical environment around the fibrils and their possible cells of origin. Glisson's sheath was found to contain 2 populations of collagen fibrils with different diameters and distinct localisations, namely fibroblast-associated and bile epithelium-associated. Fibroblast-associated collagen was composed of fibrils arranged in bundles and constituted the majority of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Considering the results in the Glisson's sheath by Hosoyamada et al (2000) the difference in diameter of collagen fibrils among the different parts of the intestinal wall probably reflect a high difference among the cells producing them. The fibroblasts in the lower LPM and TSM have distinctly different ultrastructures and different abilities to produce collagen fibrils as suggested by the different amounts of collagen fibrils.…”
Section: Morphometry Of Collagen Fibrilsmentioning
confidence: 98%
See 3 more Smart Citations
“…Considering the results in the Glisson's sheath by Hosoyamada et al (2000) the difference in diameter of collagen fibrils among the different parts of the intestinal wall probably reflect a high difference among the cells producing them. The fibroblasts in the lower LPM and TSM have distinctly different ultrastructures and different abilities to produce collagen fibrils as suggested by the different amounts of collagen fibrils.…”
Section: Morphometry Of Collagen Fibrilsmentioning
confidence: 98%
“…Recently Hosoyamada et al (2000) studied the ultrastructure of connective tissue in Glisson's sheath of the rat liver, and reported that the variations in diameter of fibrils in Glisson's sheath is related to two different components. The first, the fibril diameter, is correlated with the caliber of the bile duct, most probably corresponding to the decrease in mechanical stress along the bile duct tree.…”
Section: Morphometry Of Collagen Fibrilsmentioning
confidence: 99%
See 2 more Smart Citations
“…In liver tissue, the absorption in the visible wavelength range is dominated by hemoglobin and bile, whereas water, lipid, and collagen are the main absorbers in the near-infrared wavelength range [14,16,19]. Blood-related absorption is represented by the effective absorption coefficient for a volume of tissue containing blood vessels as μ α Blood ( λ ) = C ( λ ) c HbT μ α HbT ( λ ), where c HbT is the total hemoglobin volume fraction, StO 2 is the level of hemoglobin oxygen saturation, and μ α HbT ( λ ) = StO 2 μ α HbO 2 ( λ ) + (1 - StO 2 ) μ α Hb ( λ ).…”
Section: Methodsmentioning
confidence: 99%